Crimped monofilament nylon leader for median sternotomy closure in 10 dogs. Issue 2 (16th December 2020) - Rossanese, Matteo; Tomlinson, Andrew
Abstract: Objective: To describe and report the outcomes after closure of median sternotomies with crimped monofilament nylon leader (MNL) in dogs. Study design: Retrospective observational study. Animals: Dogs (n = 10) that underwent intrathoracic surgery through a median sternotomy approach. Methods: The median sternotomy was closed in a peristernal figure eight pattern with crimped MNL. Medical records were reviewed for clinical and histopathological findings and complications. Owners or veterinarians were contacted to collect long‐term follow‐up information. Results: The technique was simple, with no intraoperative complications. Postoperative infection was documented in one dog, requiring removal of a single MNL and associated crimp clamp. Delayed healing of the surgical incision in one dog was managed conservatively. No other complications were documented throughout long‐term follow‐up at a median of 488 days (range, 199‐608). Conclusion: Median sternotomies were successfully closed with crimped MNL and were associated with a low complication rate. Clinical significance: Crimped MNL represents an alternative method to close median sternotomies in dogs.